A severe congenital myasthenic syndrome with "dropped head" caused by novel MUSK mutations. Issue 4 (1st June 2015) - Giarrana, Miriam L.; Joset, Pascal; Sticht, Heinrich; Robb, Stephanie; Steindl, Katharina; Rauch, Anita; Klein, Andrea
ABSTRACT Introduction: Congenital myasthenic syndromes are rare. Mutations in MUSK were first described in 2004. Thirteen patients have been reported to date, mostly with a relatively mild course. The molecular diagnosis has implications for choice of treatment and genetic counseling. Methods: Clinical course and electrophysiological, pathological, and genetic findings were assessed. Results: We describe the case of a boy with prenatal onset and severe respiratory symptoms with a persisting need for ventilation. The patient had severe bulbar symptoms, marked axial weakness causing a "dropped head, " and some facial and proximal weakness. Ophthalmoparesis developed during the first year of life. Salbutamol led to improvement, 3, 4‐diaminopyridine had a modest effect, but pyridostigmine produced deterioration. Two novel mutations in MUSK were found by whole exome sequencing. Conclusions: We expand the phenotype of congenital myasthenic syndromes with MUSK mutations, describing a more severe clinical course with prenatal onset. Predominant bulbar and respiratory weakness with facial and axial weakness and ophthalmoparesis are diagnostic clues. Muscle Nerve 52: 668–673, 2015